Evaluation on East Java 100/III Regional Training Programme (PUSLATDA) 2013-2016 (An Approach towards National Sports Competition XIX-2016) - Subagio, Subagio; Irmantara, Irmantara (BIRCU, 2020)
This study aims to assess the preparation of East Java Sport Committee (KONI) to come of Multi Event National Sports Competition (PON) XIX-2016, held every 4 years. The focus of this research can be presented: 1) The process of making / designing planning East Java Puslatda 100/III; 2) The process of implementation of East Java Puslatda; 3) Compability planning and implementation of program the East Java; 4) The results of program performance East Java Puslatda East Java Puslatda 100/III. The collection data in this research was conducted through observation, study documents, interview and participation, because the researchers directly involved making planning, implementation and evaluation in East Java Puslatda 100/III. From the data are then analyzed using the CIPP methods (context, input, process and product). The results showed: 1) The East Java Puslatda 100/III for planning ideal and detail, then its implementation in first year (2013) and the second year (2014) seeking forms and in 2015 the implementation of Puslatda started in accordance with the plan expected; 4) achievement East Java Puslatda 100/III attributed the gold medal in the National Championship and PON XIX-2016 for four years showed a graph continues to rise. One model of long-term planning has been developed and implemented KONI East Java, East Java Puslatda 100 models in dealing with the planning for four years is a new innovation in preparation following the PON, and the results are relatively good. Besides preparations with a long time, which must be considered is continuity and conduciveness Puslatda organizers should be good and comfortable conditions in terms of the implementation process Puslatda must be in a state that is ideal both administratively and operationally supported and the optimal approach of sport science .